Psychological features of the professional activities of Tuvan musicians - Sandyi, Anna D.-B. (The New Research of Tuva, 2017)
Article presents the study of psychological peculiarities of professional activities of Tuvan musicians. It reviews the effect of psychological characteristics on growth of value aspects of professionalism. Author analyzes the factors that retard the development of performance and improvisation skills and level of education, discerns the openness of Tuvan musicians for innovation. In 2016 musicians of the Center for Development of Traditional Tuvan Culture and Crafts, National Orchestra of the Republic of Tuva and amateur khoomei performers were interviewed. Total number of those surveyed was 31 aged from 16 to 54, all – male. Method of acmeological research was employed. Survey also relied on methods of testing, conversation, surveillance, interview, polling. Analysis revealed that performing activities of Tuvan musicians have some peculiarities. They consist of the complex of different characteristics, conditions, factors. The most important among them are the traits of national character of Tuvans, traditions of Tuvan musical culture. Professionalism of Tuvan musicians shapes by no means only through the special musical education. Self-education that one receives by traditional ways of passing the performance practices can have no less important value. Author has already conducted such a research in relation to another professional group of Tuvan ethnos – in 2015 with pedagogues, so this time she has a chance to compare the data. Author distinguishes the elements of mentality, traits of national character that characterize the either group by virtue of ethnic identification and, in some degree, affect the professionalism of both. Dampers for professional growth are inertia, low sociability, meditativeness, self- depreciation and reluctance to innovations. Nonetheless, strong traditionalism conceived as uniqueness is perceives as a factor that promotes professionalism.